Miocene marine mammals from Portugal. Paleogeographical and paleoecological significance - Estevens, M. (2010)
Neogene marine mammals are still incompletely known in Portugal. However, a general overview of the geographic and stratigraphic distribution of marine mammal localities in the Miocene of Portugal is already possible. An attempt of correlation between the trends shown by these distributions and the horizontal and vertical environmental shifts is presented. In general, sirenians occur in deposits representing shallow, warm, low energy aquatic environments; while cetaceans are more frequent in more open, deep and temperate marine environments.